2013
DOI: 10.1007/s10532-013-9631-8
|View full text |Cite
|
Sign up to set email alerts
|

The differential stress response of adapted chromite mine isolates Bacillus subtilis and Escherichia coli and its impact on bioremediation potential

Abstract: In the current study, indigenous bacterial isolates Bacillus subtilis VITSUKMW1 and Escherichia coli VITSUKMW3 from a chromite mine were adapted to 100 mg L(-1) of Cr(VI). The phase contrast and scanning electron microscopic images showed increase in the length of adapted E. coli cells and chain formation in case of adapted B. subtilis. The presence of chromium on the surface of the bacteria was confirmed by energy dispersive X-ray spectroscopy (EDX), which was also supported by the conspicuous Cr-O peaks in F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…(Table 4). Moreover, several studies have reported utilization of chromium resistant and plant growth promoting rhizobacteria (PGPR) for the bioremediation of toxic metals (Samuel et al, 2013;Sobariu et al, 2016;Ndeddy and Babalola, 2016) to reclaim and restore soil properties.…”
Section: Morpho-physiological Characterization Of Cr(vi) Resistant Bamentioning
confidence: 99%
See 1 more Smart Citation
“…(Table 4). Moreover, several studies have reported utilization of chromium resistant and plant growth promoting rhizobacteria (PGPR) for the bioremediation of toxic metals (Samuel et al, 2013;Sobariu et al, 2016;Ndeddy and Babalola, 2016) to reclaim and restore soil properties.…”
Section: Morpho-physiological Characterization Of Cr(vi) Resistant Bamentioning
confidence: 99%
“…Such activities of soil microbes are largely affected by pollutants released to the soil, as plant growth is regulated by soil fertility (Hansda et al, 2014). Several studies have reported the utilization of plant growth promoting rhizobacteria (PGPR) for the bioremediation of toxic metals (Samuel et al, 2013;Sobariu et al, 2016;Ndeddy and Babalola, 2016 …”
Section: Introductionmentioning
confidence: 99%
“…The OD readings were taken after 12 and 24 h, since preliminary experiments with adapted and non-adapted strains showed that in both cases, these periods of time marked the end of exponential growth and the onset of the stationary phase of growth, respectively. Adaptation was assumed when growth rates and OD values of the adapted strains were significantly higher than those determined in the non-adapted strain (Samuel et al 2013).…”
Section: Isolation and Adaptation To Metalsmentioning
confidence: 99%
“…The behavior of micro-organisms toward Cr(VI) was studied previously which demonstrated the significant alleviative impact of many microorganisms, including strains of Pseudomonas, Enterobacter, Bacillus , and Shewanella (Samuel et al, 2013; Ahemad, 2015). Microorganisms were found to reduce hexavalent chromium by different mechanisms either by utilizing the hexavalent chromium as final electron acceptor or by secreting certain soluble enzymes (Samuel et al, 2013; Ahemad, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms were found to reduce hexavalent chromium by different mechanisms either by utilizing the hexavalent chromium as final electron acceptor or by secreting certain soluble enzymes (Samuel et al, 2013; Ahemad, 2015). However, the availability of efficient hexavalent chromium reducing microorganisms is a crucial requirement for the bioremediation of soils contaminated with hexavalent chromium.…”
Section: Introductionmentioning
confidence: 99%